The contribution of ehealth and mhealth to improving the performance of the health workforce: - Lapão, L (2018)
Introduction: eHealth and mHealth are technologies that allow services to be extended closer to patients, in pursuit of the objectives of Health 2020: a European policy framework and strategy for the 21st century and of the Global Strategy on Human Resources for Health: workforce 2030. As Europe faces increased demand for health services due to ageing populations, rising patient mobility, and a diminishing supply of health workers caused by retirement rates that surpass recruitment rates, this paper illustrates how eHealth and mHealth can improve the delivery of services by the health workforce in response to increasing demands. Methods: Through a scoping literature review, the impact of eHealth/mHealth on the health workforce was assessed by examining how these technologies affect four dimensions of the performance of health professionals, according to the so-called AAAQ: availability, accessibility, acceptability, and quality. Results: Few high-quality studies were found. Most studies focused on the utilization of text messaging (SMS) for patient behavior change, and some examined the potential of mhealth to strengthen health systems. We also found some limited literature reporting effects on clinical effectiveness, costs, and patient acceptability; we found none reporting on equity and safety issues. Facilitators and barriers to the optimal utilization of eHealth and mHealth were identified and categorized as they relate to individuals, professional groups, provider organizations, and the institutional environment. Discussion: There are ongoing clinical trial protocols of largescale, multidimensional mHealth interventions, suggesting that the current limited evidence base will expand in coming years. The requirement for new digital skills for human resources for health (HRH) was observed as significant. This has implications for the education of health workers, the management of health services, policy-making, and research.